SMAD-dependent signaling mediates morphogenetic protein 6-induced stimulation of connective tissue growth factor in luteinized human granulosa cells. Issue 2 (18th June 2019) - Liu, Shuang; Chang, Hsun-Ming; Yi, Yuyin; Yao, Yuan-Qing; Leung, Peter C K
Abstract: Connective tissue growth factor (also known as CTGF or CCN2) is a secreted matricellular protein that belongs to the CCN family. With wide-ranging biological activities and tissue expression patterns, CTGF plays a critical role in regulating various cellular functions. In the female reproductive system, CTGF is highly expressed in granulosa cells in growing ovarian follicles and is involved in the regulation of follicular development, ovulation, and luteal function. In the mammalian ovary, bone morphogenetic protein 6 (BMP6) is an important intraovarian modulator of follicular development. In this study, we demonstrated that BMP6 treatment significantly increased the expression of CTGF in both primary and immortalized human granulosa cells. Using both pharmacological inhibitors and Small interfering RNA-mediated knockdown approaches, we showed that ALK2 and ALK3 type I receptors are required for BMP6-induced cellular activities. Furthermore, this effect is most likely mediated by a Sma- and Mad-related protein (SMAD)-dependent pathway. Our studies provide novel insight into the molecular mechanisms by which an intraovarian growth factor affects the production of another factor via a paracrine effect in human granulosa cells. Abstract : BMP6 induces the expression of CTGF, which is most likely mediated by an ALK2/ALK3-SMAD dependent signaling pathway in human granulosa cells.